Hockey Skills Book Development - Ibrahim, Ibrahim; Manik, Syahputra; Gultom, Siti Rahima (Budapest International Research and Critics University, 2021)
This research and development aims 1) to develop a guidebook for basic techniques in the game of hockey and produce a new book that emphasizes the correctness of motion according to current needs as an instructional of basic techniques in the game of hockey. This study uses the Research & Development (R & D) method using the Willis R2D2 development procedure which consists of 3 focuses (1. Focus on determination, 2. Focus on design and development, 3. Focus on dissemination). The data collection technique used a summative evaluation questionnaire sheet. The instrument used was a summative evaluation questionnaire of media experts and material experts to determine the feasibility of the book. The data analysis technique used in research and development is descriptive quantitative to process data in the form of assessment scores by media experts and material experts. The results of the study were based on the assessment of media experts in the aspect of the book cover, 92% in the appropriate category, the content aspect in the book 86% in the appropriate category, the material expert in the foreword aspect with a percentage of 80% in the appropriate category, the content aspect in the book 91.6% in the appropriate category, the list aspect library 90% with decent category, 80% keyword aspect with decent category, 90% attachment aspect with decent category. Based on the results of the summative evaluation, the product developed is feasible to use. material expert for the foreword aspect with a percentage of 80% in the appropriate category, 91.6% in the book content aspect in the appropriate category, the bibliography aspect with 90% in the appropriate category, 80% in the keyword aspect in the appropriate category, 90% in the attachment aspect in the appropriate category.